"I came all this way to receive training, am I really going to be taught by a woman?" Factors that support and hinder women's participation in agroecology in Costa Rica. Issue 7 (9th August 2021) - Sylvester, Olivia; Little, Mary
ABSTRACT: In agroecology, women's activities, from seed saving to activism, are well documented. Less well described are the factors that support and/or hinder women's participation in agroecology; we addressed this gap through a feminist analysis of women's motivations and barriers to participation in agroecological production in Costa Rica. We found that women derive multiple benefits from agroecology. These benefits included: sharing knowledge, creating community, income generation, independence (financial and having their own identity that goes beyond that of a man's), cultural identity, health (human and land), biodiversity conservation, self-confidence, and leadership opportunities within agroecological networks. Our results also illustrated how there are multiple barriers to women's participation including: access to leadership positions, government support, access to capital, technology, land access, high costs of agriculture, a lack of understanding of Indigenous culture, triple burdens, and machismo and microaggressions. Although women experienced some common barriers to participation, women experience agroecology differently, based on age, ethnicity, and geographic location, and their unique context. The common barriers reported by women (machismo and triple burdens) illustrate how agroecology cannot be isolated from 1) the wider culture of discrimination against women in agriculture and 2) women's disproportionate roles in the care economy.